An investigation on the construction methods and recommended retrofitting techniques on selected heritage churches in Region 4A - Calabarzon - Cruz, Jose Vincent E.; Roque, Melvin Rei C.
Built heritage includes buildings and structures that require conservation and are of historical or cultural importance. The Philippines is prone to earthquakes which can damage unreinforced masonry (URM) structures. Information on the construction methods of these structures will be needed in order to provide retrofitting plans. This study aims to identify construction methods and techniques of heritages churches, to classify them into certain typologies, and to recommend retrofitting technologies appropriate to these structures depending on the type of structure, material, method of construction and other parameters. Eleven URM heritage churches, built during the 18th and 19th century, were selected in Region 4A. Site visits were done to perform investigation on the churches including sketching of a floor plan. The construction methods that were identified include wall construction, arch construction, wall-to-roof connections, doorways and windows construction, and roof member connections. The churches were classified according to geometry, roof truss system, masonry type and presence of buttresses. Buttresses were observed to be present on most churches built from the late 17th century up to mid-18th century. Suggested retrofitting techniques for the churches only include grouting, structural repointing, confinement, FRP reinforcement, mesh reinforcement and shotcreting since they were determined only through visual inspection. More complex and innovative techniques would require in-depth analysis on the structures including supervision of a professional.